Konsep Pelaksanaan Hibah Bagi Kes-kes Maradh Al-Mawt COVID-19 Dalam Kalangan Orang Islam Di Malaysia - Wan Abdul Fattah Wan Ismail; Mohd Radzniwan A Rashid; Muhammad Aunurrochim Mas'ad Saleh; Lukman Abdul Mutalib; Syahirah Abdul Shukor; Zulfaqar Mamat; Ahmad Syukran Baharuddin; Norma Jusof; Mohamad Aniq Aiman Alias (USIM Press, 2024)
Vol. 9 No. 1 (2021): MJSL - Volume 9, No. 1, 2021